2020
DOI: 10.1186/s12917-020-02653-4
|View full text |Cite
|
Sign up to set email alerts
|

Supranutritional selenium level minimizes high concentrate diet-induced epithelial injury by alleviating oxidative stress and apoptosis in colon of goat

Abstract: Background High concentrate (HC) diet-induced oxidative stress causes gut epithelial damages associated with apoptosis. Selenium (Se) being an integral component of glutathione peroxidase (GSH-Px) plays an important role in antioxidant defense system. Therefore, increasing dietary Se level would alleviate HC diet-induced injuries in gut mucosa. The present study investigated eighteen cross-bred goats, randomly divided into three groups (n = 6/group) fed either low concentrate (LC, roughage: con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 61 publications
2
10
1
Order By: Relevance
“…Though LPS levels raised in both HC and HCSe goats, but LPS levels were significantly lower by 22 .35% and 37.68% in colon and serum of HCSe goats, respectively. Similar findings have been reported by previous studies in goats (Samo et al, 2020 ). However, the exact mechanism of lowering LPS levels by Se supplementation is not known.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Though LPS levels raised in both HC and HCSe goats, but LPS levels were significantly lower by 22 .35% and 37.68% in colon and serum of HCSe goats, respectively. Similar findings have been reported by previous studies in goats (Samo et al, 2020 ). However, the exact mechanism of lowering LPS levels by Se supplementation is not known.…”
Section: Discussionsupporting
confidence: 93%
“…The increase in acetate concentration and acetate propionate ratio by 49.21% and 20.35 along with reduced pH suggest that fermentation process was negatively affected in HC compared with LC goats (Huhtanen et al, 1993 ). However, Se addition improved fermentation in HCSe compared with HC goats, which is consistent with findings of Samo et al ( 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Samo et al (2020) revealed that long-term HC diet feeding can induce epithelial injury and apoptosis in the colon. In the present study (42) , Bax mRNA levels were significantly decreased, whereas the Bcl-2 mRNA level and the Bcl2/bax ratio were significantly increased in HCT goats compare to that in the HC goats. Moreover, the results of enzyme activity analysis in colonic mucosa showed that the HCT group had a markedly decrease in caspase-3, caspase-8 enzyme activity compared with the only HC diet feeding, which suggests that thiamine contributes to the attenuation of the HC diet-induced apoptosis through regulation of the Bax/Bcl-2 ratio and the caspase pathway.…”
Section: Discussioncontrasting
confidence: 42%